2017
DOI: 10.7717/peerj.3450
|View full text |Cite
|
Sign up to set email alerts
|

Diversity analysis of gut microbiota in osteoporosis and osteopenia patients

Abstract: Some evidence suggests that bone health can be regulated by gut microbiota. To better understand this, we performed 16S ribosomal RNA sequencing to analyze the intestinal microbial diversity in primary osteoporosis (OP) patients, osteopenia (ON) patients and normal controls (NC). We observed an inverse correlation between the number of bacterial taxa and the value of bone mineral density. The diversity estimators in the OP and ON groups were increased compared with those in the NC group. Beta diversity analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
150
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(180 citation statements)
references
References 33 publications
12
150
4
3
Order By: Relevance
“…The changes of composition and abundance of microbiota have been linked with many inflammatory and metabolic disorders, such as inflammatory bowel disease, rheumatoid arthritis, type 2 diabetes, and obesity (Ley et al, 2006;Frank et al, 2007;Qin et al, 2012;Zhang et al, 2015). More recently, Wang et al conducted a 16S rRNA gene sequencing to detect the composition and diversity changes of gut microbiota in patients with primary osteoporosis and primary osteopenia (Wang et al, 2017). The results suggest that compared with normal controls, the bacterial composition and diversity are altered in osteoporosis and osteopenia patients, which supported the view that the bone health might be influenced by the gut microbiota (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The changes of composition and abundance of microbiota have been linked with many inflammatory and metabolic disorders, such as inflammatory bowel disease, rheumatoid arthritis, type 2 diabetes, and obesity (Ley et al, 2006;Frank et al, 2007;Qin et al, 2012;Zhang et al, 2015). More recently, Wang et al conducted a 16S rRNA gene sequencing to detect the composition and diversity changes of gut microbiota in patients with primary osteoporosis and primary osteopenia (Wang et al, 2017). The results suggest that compared with normal controls, the bacterial composition and diversity are altered in osteoporosis and osteopenia patients, which supported the view that the bone health might be influenced by the gut microbiota (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we found an increased abundance of Bacteroides genus in osteoporosis group, which is consistent with previous report (11). Bacteroides is one of the most dominant genera in both osteoporotic individuals and normal subjects samples (10). As previously reported, Bacteroidetes might be involved in bone formation and bone resorption by deposition and hydrolysis of serine dipeptide lipids (18).…”
Section: Discussionmentioning
confidence: 99%
“…Das et al reported there were differences of gut microbiota composition between osteoporosis /osteopenia and controls with an Irish cohort of older adults (9). Wang et al analyzed the gut microbiota diversity in a relatively small sample with 6 primary osteoporosis patients, 6 osteopenia patients and 6 healthy controls (10). Li et al identified several differential fecal bacterial taxa from patients with low bone mineral density (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, to date there is only one report linking the microbiome to osteoporosis in humans: the gut flora in patients with osteoporosis (defined using bone mineral density (BMD)) was recently reported to be different from that of normal controls (microbiota assessed by analysis of fecal 16S rRNA) [28]. While the report is clearly limited by a small sample size (n=6/group), it does support the idea that osteoporosis is associated with changes in the gut microbiota.…”
Section: Bonementioning
confidence: 99%